WorldFish silver carp Generation 2 families produced (2022) - Hamilton, Matthew; Akhter, Md; Roy, Aashish Kumar; Sarkar, Uzzal Kumar; Kundu, Ramprosad; Rahman, Md. Mustafizur; Shanta, Sirajum Monira; Kamruzzaman, Md.; Hossain, Jamal; Hossain, Md.; Haque, Mojammel; Sarkar, Anutosh; et al. (2023)
WorldFish manages family-based selective breeding programs for three carp species: catla (Catla catla), rohu (Labeo rohita) and silver carp (Hypophthalmichthys molitrix). WorldFish carp genetic improvement programs aim to substantially increase aquaculture productivity in Bangladesh by developing and disseminating rapidly growing strains to farmers. This dataset details the WorldFish silver carp generation-two (G2) families produced in the 2022 spawning season.